Lead-free ferroelectric material: Dysprosium doped Bi4Ti 3O12 - Thongmee N. (2014)
This study investigated fundamental of phase formation, crystal structure and calcination process for bismuth dysprosium titanate (Bi4-xDy xTi3O12; BDT) powders when x = 0, 0.25, 0.5, 0.75 and 1.0. BDT powders were prepared using a simple solid-state reaction on mixtures of reagent grade Bi2O3, Dy2O 3 and TiO2 powders. The mixtures were calcined at temperature in the range of 500-800°C for 4 h at a heating/cooling rate of 5°C/min. Thermal characteristics of powders were studied using thermogravimetric/differential thermal analyses which indicated that the formation of Bi4Ti3O12 and Bi 3Dy1Ti3O12 powders occurred at -500°C. Effect of Dy3+ concentration on phase and crystal structure was investigated using X-ray diffractometry. The results revealed that at small concentration of Dy dopant (x ≤ 0.25), optimum calcination temperature for providing bismuth titanate-based phase was 650°C. Increasing content of Dy dopant seemed to reduce calcination temperature to 600°C. This study suggested the alternative environmental friendly BDT materials which may be used as starting powders for production of high quality BDT ceramics. © 2008 Trans Tech Publications, Switzerland.